2009
DOI: 10.1007/s12161-009-9115-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment on the Amplification and Quantification of Transgenic and Non-transgenic Soybean and Maize DNA

Abstract: Processing of raw plant materials causes occurrence of degraded DNA in foods. The effect of DNA degradation on amplification and quantification of transgenic and non-transgenic DNA in raw and experimentally thermally processed foods was studied. The degree of DNA degradation was checked by agarose gel electrophoresis and polymerase chain reaction (PCR). Cetyl trimethyl ammonium bromide method yielded DNA of a better quality, while Genespin and Wizard were less appropriate. Baking at 220°C considerably reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
4
27
2
4
Order By: Relevance
“…Although the purity values of the extracts that we obtained were between 1.06 and 1.34, the detection of the lectin sequence in all the extracts proved that they contain amplifiable quality DNA. Similar to our results, the purity values of the DNA extracts that Bergerova et al (2010) obtained from baked soy flour samples were between 1.10 and 1.38.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Although the purity values of the extracts that we obtained were between 1.06 and 1.34, the detection of the lectin sequence in all the extracts proved that they contain amplifiable quality DNA. Similar to our results, the purity values of the DNA extracts that Bergerova et al (2010) obtained from baked soy flour samples were between 1.10 and 1.38.…”
Section: Resultssupporting
confidence: 90%
“…The mean DNA concentration that we obtained with the Wizard ® Magnetic DNA Purification System for Food was 84.8-213 ng/µL (Table 1). These values were significantly higher from those reported by Bergerova et al (2010), who reported that the DNA concentration they could obtain with the same method was 20-70 ng/µL. This difference may be attributable to the higher sample portion that we used.…”
Section: Resultscontrasting
confidence: 76%
See 3 more Smart Citations